PENGARUH KEPUASAN KERJA, KINERJA, SIKAP TERHADAP PEKERJAAN DAN KOMITMEN ORGANISASI DI PT. SEPANJANG BAUT SEJAHTERA KOTA SURABAYA. - CHINTHIA T, DEBBY (Universitas Katolik Widya Mandala Surabaya, 2013)
This study aimed to clarify the influence of organizational commitment on job satisfaction and job performance, attitude toward work to influence job satisfaction and job performance and job satisfaction influences job performance terhada. The object of this study is PT Throughout Bolt Prosperity in Surabaya. The number of research samples, 150 samples but outlier analysis identified that there were 12 respondents to the answers diverge, so the number of the next sample is 138 samples. Data analysis techniques using structiral equation models with LISREL program. The findings in this study indicate that organizational commitment and attitude toward work proven effect on job satisfaction. Organizational commitment shown to affect the job performance, but the attitude toward work is not proven effect on job performance. Job satisfaction evident effect on job performance. To that end, the first research hypothesis states that job satisfaction affects job performance is proven.